2019
DOI: 10.1111/jcpe.13205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐surgical periodontal therapy on inflammatory markers of psoriasis: A randomized controlled trial

Abstract: Aim The purpose of this randomized controlled clinical study was to evaluate the effect of non‐surgical mechanical periodontal therapy on the inflammatory status and severity of psoriasis in subjects with psoriasis. Material and methods The study population consisted of 92 periodontitis patients with psoriasis vulgaris suffering from an untreated periodontal disease. Two randomized groups were formed from these patients: immediate periodontal therapy (test group, n = 46) and delayed periodontal therapy (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This finding is in line Fadel et al, 15 although both groups of their study showed a suboptimal oral hygiene level. Although Skudutyte-Rysstad et al 12 and Yarkac et al 24 observed significantly higher mean values of BOP in the psoriasis group, Kathariya and Pradeep 23 observed that PI and gingival index were significantly higher in the psoriasis group. In our study, 80% of the patients in the case group were using a systematic immunosuppressive medication.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is in line Fadel et al, 15 although both groups of their study showed a suboptimal oral hygiene level. Although Skudutyte-Rysstad et al 12 and Yarkac et al 24 observed significantly higher mean values of BOP in the psoriasis group, Kathariya and Pradeep 23 observed that PI and gingival index were significantly higher in the psoriasis group. In our study, 80% of the patients in the case group were using a systematic immunosuppressive medication.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, effective periodontal therapy in psoriatic patients may improve the skin condition, which Ucan Yarkac et al . showed in their study 22 . The co‐occurrence of psoriasis and periodontitis affects the quality of life and the negative impact increases with the severity of both diseases 23 .…”
Section: Discussionmentioning
confidence: 93%
“…The elimination of inflammation foci in the oral cavity is essential in order to avoid psoriasis exacerbation and harmful side effects of systemic and biological agents 3,12 . Only nine subjects (7.1%) required periodontal therapy compared to the findings of Szpak (19.8%), which seems to be a good outcome according to Ucan Yarkac 22,26 …”
Section: Discussionmentioning
confidence: 98%
“…proposed that periodontitis may play a direct or indirect role in the occurrence or exacerbation of PsO through the immunomodulatory effect of oral microbiota, and may affect the efficacy of anti-PsO treatment ( 94 ). Periodontal basic treatment can reduce the severity of PsO while improving periodontal status and reducing the expression level of inflammatory factors in saliva ( 95 ). Treatment of PsO with TNF-α inhibitors can also slow down the progression of periodontitis ( 96 ).…”
Section: Role Of Il-17a In the Relationship Between Periodontitis And...mentioning
confidence: 99%